2002
DOI: 10.1161/01.hyp.0000036396.64769.c2
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and Antiarteriosclerotic Effects of Pioglitazone

Abstract: Abstract-Peroxisome proliferator-activated receptor-␥ (PPAR␥) ligands are widely used in patients with insulin resistance and diabetes. Because coronary artery disease is a major complication for such patients, it is important to determine the effects of PPAR␥ activation on arteriosclerosis. Long-term inhibition of endothelial NO synthesis by administration of N -nitro-L-arginine methyl ester (L-NAME) to rats induces coronary vascular inflammation (monocyte infiltration, monocyte chemoattractant protein-1 [MCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 51 publications
5
75
0
1
Order By: Relevance
“…The telmisartan dose of 1 mg/kg per day in the present study may have weakly stimulated PPARγ. A typical PPARγ ligand, pyoglitazone, significantly reduced vascular ACE activity in a N ω -nitro-L-arginine methyl esterinduced hypertensive model (27), and the dose of telmisartan also reduced vascular ACE activity in the present study. On the other hand, Imayama et al (28) demonstrated that pyoglitazone and telmisartan, a partial PPARγ agonist, significantly reduced AT1 receptor expression in cultured rat vascular smooth muscle cells, but that the non-PPARγ agonists olmesartan and candesartan did not.…”
Section: Fig 5 Ace Activities In Wky Rats Placebo (P)- Telmisartasupporting
confidence: 68%
“…The telmisartan dose of 1 mg/kg per day in the present study may have weakly stimulated PPARγ. A typical PPARγ ligand, pyoglitazone, significantly reduced vascular ACE activity in a N ω -nitro-L-arginine methyl esterinduced hypertensive model (27), and the dose of telmisartan also reduced vascular ACE activity in the present study. On the other hand, Imayama et al (28) demonstrated that pyoglitazone and telmisartan, a partial PPARγ agonist, significantly reduced AT1 receptor expression in cultured rat vascular smooth muscle cells, but that the non-PPARγ agonists olmesartan and candesartan did not.…”
Section: Fig 5 Ace Activities In Wky Rats Placebo (P)- Telmisartasupporting
confidence: 68%
“…41 In addition, PPAR␥ agonists inhibit CCR2 expression in monocytes and atherosclerosis development in rats. 42,43 Thus, PPAR␥-mediated CCR2 expression by macrophages may be an important pathway in atherogenesis and provides a novel therapeutic target for prevention or treatment of atherosclerosis.…”
Section: Babaev Et Al Role Of Macrophage Ppar␥ In Atherosclerosis 1651mentioning
confidence: 99%
“…However, it is unclear if the beneficial effects of these agents are based primarily on decreasing insulin resistance, because the PPAR␥ agonists have anti-inflammatory, anti-fibrotic as well as other metabolic activities. 13,14 The aim of the current study was to characterize the biochemical, metabolic, and histological changes that occur after pioglitazone is discontinued in a cohort of patients who demonstrated significant improvement in these parameters during therapy.…”
mentioning
confidence: 99%